Endothelium‐Independent Relaxant Effect of Rubus Coreanus Extracts in Corpus Cavernosum Smooth Muscle. (13th May 2013) - Lee, Jun Ho; Chae, Mee Ree; Sung, Hyun Hwan; Ko, Mikyeong; Kang, Su Jeong; Lee, Sung Won
Abstract Introduction Rubus coreanus is a perennial shrub native to the southern part of the Korean peninsula. Although it is known that R. coreanus has a dose‐dependent relaxation effect on rabbit corpus cavernosum (CC), the exact mechanism of action by which R. coreanus work is not fully known. Aims To elucidate the direct effects of unripe R. coreanus extract (RCE) on CC smooth muscle cells. Methods Dried unripe R. coreanus fruits were pulverized and extracted with 95% ethanol. Isolated rabbit CC strips were mounted in an organ‐bath system, and the effects of RCE were evaluated. To estimate [Ca2+]i, we used a Fura‐2 fluorescent technique. Main Outcome Measures The effects of unripe RCE on ion channels and the intracellular Ca2+ concentration ([Ca2+]i) of CC. Results RCE effectively relaxed phenylephrine (PE)‐induced tone in rabbit CC, and removal of the endothelium did not completely abolish the relaxation effect of RCE. Tetraethylammonium (1 mM) did not inhibit RCE‐induced relaxation in strips precontracted by PE in the organ bath. However, CaCl2‐induced constriction of CC strips, bathed in Ca2+‐free buffer and primed with PE, was abolished by RCE. In addition, RCE decreased basal [Ca2+]i in corporal smooth muscle cells. The increases of [Ca2+]i evoked by 60 mM K+‐containing solution in A7r5 cells were suppressed by RCE, and RCE relaxed KCl‐induced tone in endothelium‐free CC, which indicated that RCE blocked the voltage‐dependent Ca2+ channels (VDCCs). RCE decreased basal [Ca2+]i and the [Arg8]‐vasopressin‐induced [Ca2+]i increases in A7r5 cells, and RCE inhibited the contraction of endothelium‐free CC induced by PE in Ca2+‐free solution, which suggested that RCE might act as a modulator of corporal smooth muscle cell tone by inhibiting Ca2+ release from sarcoplasmic reticulum. Conclusion RCE acts through endothelium‐independent and endothelium‐dependent pathways to relax CC. RCE may inhibit VDCCs and Ca2+ release from sarcoplasmic reticulum. Lee JH, Chae MR, Sung HH, Ko M, Kang SJ, and Lee SW. Endothelium‐independent relaxant effect ofRubus coreanusextracts in corpus cavernosum smooth muscle. J Sex Med **;**:**–**.